Preparation of sepiolite modified MXene composite membrane for oil/water separation. Issue 29 (20th May 2022) - Zhang, Lei; Zhao, Yong; Deng, Zhibin; Liu, Xiang; Chen, Yonggang; Zhang, Jun; Liu, Yongcong; Zeng, Guangyong
Abstract: Oily wastewater has caused serious damage to the ecological environment and became one of the main factors hindering the sustainable development of human society. Novel membrane materials are expected to be an effective way to solve the pollution due to its high separation efficiency. In this work, sepiolite (Sep), a natural inorganic clay material, was inserted into the adjacent MXene nanosheets, and a series of Sep@MXene/CA composite membranes were successfully constructed on the cellulose acetate (CA) commercial membrane through vacuum filtration method. The structure of nanomaterials and composite membranes were characterized by X‐ray diffraction and scanning electron microscopy. The permeability and selectivity of Sep@MXene/CA composite membranes for lubricating oil emulsion were investigated in detail. The results showed that the modified composite membranes exhibited better hydrophilicity compared with pure MXene/CA membrane, which presented pure water flux of 611.2 and 820.3 L m −2 h −1 bar −1, respectively. In addition, the rejection ratio of lubricating oil was more than 95%. This work provides a new approach for the modification of MXene membrane and makes Sep@MXene/CA membrane show a good application potential for the treatment of oily wastewater. Abstract : Sep nanoparticles played a positive role in expanding the interlayer spacing of MXene as well as providing more channels for water molecules permeating through membrane. However, the interlayer spacing of MXene nanosheets was still smaller than the oil droplet size, which ensured the selectivity of the composite membrane. This membrane overcomes the trade‐off effect between permeability and selectivity of membrane materials.